SYSTEMATIC LITERATURE REVIEW ON ARTIFICIAL INTELLIGENCE IN INDONESIA’S PUBLIC SECTOR: REIMAGINING DIGITAL GOVERNMENT - Pratiwi, Aprilia; Rahmawyanet, Mahsa Elvina; Wibowo Putra, Prasetyo Adi; Sensuse, Dana Indra (LPPM Nusa Mandiri, 2025)
This study conducts a Systematic Literature Review (SLR) to critically examine the application of Artificial Intelligence (AI) in e-government within the Indonesian public sector. Addressing the limited empirical research and fragmented understanding of AI adoption in Indonesia’s digital governance landscape, this review analyzes 22 peer reviewed articles published between 2021 and 2025 from reputable databases including Scopus, IEEE, ACM Digital Library, SpringerLink, and Emerald Insight. The review identifies adaptability and innovation, ethical consideration, collaboration and partnership as the most frequently cited critical success factors. Meanwhile, the top three recurring challenges are lack of awareness, skill & expertise, policy or legal uncertainty, resistance to change. To address these challenges, the study proposes a multi dimensional AI implementation strategy focusing on strengthening digital infrastructure, developing human capital through sustained capacity building, formulating clear and accountable AI governance policies, and fostering inclusive, cross sectoral stakeholder engagement. This study offers novel insights by mapping AI related factors into the Technology,Organization, Environment (TOE) framework and synthesizing practical, context-specific recommendations for Indonesian policymakers seeking to build an adaptive, inclusive, and sustainable AI based e-government ecosystem